A feasibility study of cell phone and landline phone interviews for monitoring of risk and protection factors for chronic diseases in Brazil - Erly Catarina Moura; Rafael Moreira Claro; Regina Bernal; Juliano Ribeiro; Deborah Carvalho Malta; Otaliba Morais Neto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The study objective was to evaluate the feasibility of interviews by cell phone as a complement to interviews by landline to estimate risk and protection factors for chronic non-communicable diseases. Adult cell phone users were evaluated by random digit dialing. Questions asked were: age, sex, education, race, marital status, ownership of landline and cell phones, health condition, weight and height, medical diagnosis of hypertension and diabetes, physical activity, diet, binge drinking and smoking. The estimates were calculated using post-stratification weights. The cell phone interview system showed a reduced capacity to reach elderly and low educated populations. The estimates of the risk and protection factors for chronic non-communicable diseases in cell phone interviews were equal to the estimates obtained by landline phone. Eligibility, success and refusal rates using the cell phone system were lower than those of the landline system, but loss and cost were much higher, suggesting it is unsatisfactory as a complementary method in such a context.